Mette Leonard Høeg, editor. Literary Theories of Uncertainty. Bloomsbury, 2021. - Samantha Lepak (Studies in 20th & 21st Century Literature, 2022)
Review of Mette Leonard Høeg, editor. Literary Theories of Uncertainty. Bloomsbury, 2021. xi + 295 pp.
Keywords: uncertainty; literary theory; deconstruction; literary criticism; semantics